The peculiarities of particle dynamics in the Fermi acceleration scheme - Buts, V.A. (Вопросы атомной науки и техники, 2015)
With examples of discrete and distributed mathematical models of the Fermi acceleration mechanism, a usefulness, or even necessity, of taking into account of singular solutions is demonstrated. Also the role is shown of those parts of phase space where the uniqueness theorem conditions to form the dynamics of physical systems are broken. It was found that the dynamics of particles in discrete and distributed mathematical schemes of Fermi acceleration can be significantly different. The difference is due to the fact that the distributed model takes into account the effects of phase space where conditions do not correspond to those necessary for application of the uniqueness theorem. The role of singular solutions is under discussion as well.